Foster Indonesian Diversity from School by Building the Character of Pancasila Students - Nurani, Sri (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
Caring for the Diversity of Schools by Building the Character of Pancasila Students. The background is the phenomenon of viral news related to the issue of the dynamics of diversity in the educational environment. This news quickly spread to become a hot issue that was feared could have a negative impact. Because the Indonesian nation stands on a foundation of diversity / diversity, this condition is a problem that must be resolved so that it does not develop into a bigger conflict while preventing and minimizing it. The research method used qualitative methods with data collection techniques through observation, literature study and interviews. The results of the research show that there is an assumption that diversity / diversity can endanger the integrity of the nation, is a reason to maintain diversity in order to remain in wholeness and unity. Schools as intellectual communities and as miniatures of national diversity must be able to care for this diversity by building the character of Pancasila students. Pancasila students are lifelong students who have global competence and behave according to the values of Pancasila, namely: Believing & being devoted to God Almighty and Moral Morals, Global Diversity, Mutual Cooperation, Independent, Critical Reason, Creative.